Holzbrücke beim Teich auf dem Gelände des "Casale al Bivio", Brione s. Minusio
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Friedensbewegung politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Jugendbewegung